The scale of parental playfulness attitude (PaPA): evaluating the psychometric properties with Latino caregivers in the U.S. - Goertzen, Kayley Michelle, author; Bundy, Anita, advisor; Lane, Shelly, committee member; Reinke, Jennifer, committee member; Yuma, Paula, committee member (Colorado State University. Libraries, 2021)
Play is a meaningful occupation for individuals across the lifespan. Often, play occurs in the context of caregiver-child joint play in which the playfulness of the caregiver can be a support or a barrier to the child's play participation. Occupational therapists (OTs) who seek to optimize performance and participation in joint play must consider the caregiver's level of playfulness when designing interventions. Any measure of caregiver playfulness must be valid and reliable for a given client population. OTs often work with clients from the growing and diverse Latino population in the U.S. Review of literature reveals few measurement tools assess caregiver playfulness, and none have been validated for the Latino American population. To this end, I administered the Scale for Parental Playfulness Attitude (PaPA; Román-Oyola et al., 2019) to 50 Latino American caregivers of children between 29 and 85 months old. Data collected with the PaPA demonstrated preliminary evidence for construct validity (positive point-measure correlations, 93% of items fit Rasch expectations, 4.46 eigenvalues in principal components analysis contrast, consistent rating scale, limited item spread, logical item hierarchy), excellent evidence for internal reliability (person-reliability index = 0.85, strata = 3.55), and good evidence cross-cultural validity (25/28 or 89% of items formed similar hierarchy for participants in the U.S. and Puerto Rico). The findings of this study suggest the PaPA may be useful to establish a baseline measure of caregiver playfulness, show change in playfulness over time, and guide interventions to promote quality performance and participation in the co-occupation of joint play.
Keywords: Latino; play; Rasch; measurement; instrument; playfulness